2017
DOI: 10.4103/1319-2442.206443
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of acute glomerulonephritis in adult population in Dubai: A single-center experience

Abstract: Epidemiological data of renal diseases have great geographic variability throughout the world. Due to the lack of a national renal data registry system, there is no information on the prevalence rate, clinical and pathological features of various glomerulonephritis (GN) in the United Arab Emirates (UAE). In a retrospective cross-sectional study, we analyzed 158 renal biopsies done in Dubai Hospital, UAE, between the years of 2005 and September 2014, with an aim to determine the prevalence rate and frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…MPGN and mesangial proliferative GN were each reported in 4.3% of our patients, and these were less prevalent in our cohort compared with that in earlier studies [ 8 – 10 ] owing to an improved infection control; similar results have been reported in recent data from Saudi Arabia [ 22 ] and Dubai [ 21 ].…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…MPGN and mesangial proliferative GN were each reported in 4.3% of our patients, and these were less prevalent in our cohort compared with that in earlier studies [ 8 – 10 ] owing to an improved infection control; similar results have been reported in recent data from Saudi Arabia [ 22 ] and Dubai [ 21 ].…”
Section: Methodssupporting
confidence: 89%
“…As noted in our study, the high-grade proteinuria with or without renal impairment was the clinical indication of kidney biopsy. Among the neighboring countries of Jordan, Qatar has a diabetic nephropathy prevalence of 50% of secondary GN [ 20 ], and Dubai has a diabetic nephropathy prevalence of 14% of secondary GN and 4.4% of GN [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…17–19 Interestingly, in one of these studies, LN had the highest incidence among all types of glomerular diseases, even the primary ones. 18…”
Section: The Demographics Of Ln and Ln Morbidity In The Uaementioning
confidence: 99%
“…16 In the UAE, several retrospective studies on the pattern of biopsy-proven renal disease in patients revealed a similar conclusion that LN is the major cause of secondary glomerular disease. [17][18][19] Interestingly, in one of these studies, LN had the highest incidence among all types of glomerular diseases, even the primary ones. 18 End-stage renal disease (ESRD) is the most serious consequence of LN.…”
Section: The Demographics Of Ln and Ln Morbidity In The Uaementioning
confidence: 99%
See 1 more Smart Citation